An Analysis of Digital Education in Canada in 2017-2019 - Veletsianos, George; VanLeeuwen, Charlene A.; Belikov, Olga; Johnson, Nicole (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
Digital education refers to in-person, blended, and fully online learning efforts, as well as attempts to capture a wide range of teaching and learning contexts which make use of digital technology. While digital education is pervasive in Canada, pan-Canadian data on digital education are relatively scarce. The Canadian Digital Learning Research Association/Association Canadienne de Recherche sur la Formation en Ligne conducted pan-Canadian surveys of higher education institutions (2017-2019), collecting data on the digital education landscape and publishing annual reports of its results. Previous analyses of the data have used quantitative approaches. However, the surveys also collected responses to open-ended questions. In this study, we report a systematic analysis of qualitative data exploring the digital education landscape in Canada and its changes over time. Findings shed light on the growth of digital education, the situated and multidimensional nature of digital education, the adoption of openness, quality, and rigour, and the development of alternative credentials.